The Efficiency of Tax Collection in the Czech Republic - Tomášková, Eva (Public Governance, Administration and Finances Law Review, 2020)
This paper deals with the efficiency of tax collection in the Czech Republic. The first part of this paper describes theoretical approaches to efficiency of taxes. Considering the aim of the article, there are no mathematical models of efficiency presented. The second part introduces efficiency from the point of view of law. The next part involves the application of efficiency of tax collection, especially how to measure efficiency and the main barriers for its establishment in the Czech Republic. The last part of the paper offers the summing up of gained knowledge. The aim of this paper is to detect if the current approach to tax collection contributes to higher efficiency.